Uma abordagem orientada a modelos e para engenharia de requisitos de sistemas de sistemas - Duarte, Felipe Lima (Universidade Federal Rural do Semi-Árido, 2018)
A system of systems can be seen as a set of independent constituent systems that interact with each other to accomplish a common mission, as well as deliver complex functionality to the end user. Requirements engineering is a systematic and disciplined approach to specification and management of the requirements of a software or system. It aims to elicit, model and manage the main functionalities and constraints of the system, in addition to establishing a consensus among stakeholders. Model-driven engineering is a software development approach that has in the models the key entities of development. The models can describe various aspects of the software, such as features, restrictions, maintenance, among others. In this context, the main objective of this work is to present a requirements engineering approach for systems systems that benefits from model orientation and can be used to define the missions of these systems, as well as derive and model the requirements of their constituent systems. The conduction of this work was guided by the paradigm Design Science and the research-action methodology. To demonstrate the use of the latter, two versions of the approach are presented, the initial version, called REAp-SoS; and the final version, called MORE-SoS. To validate the approaches, they were used to specify and model the requirements of two distinct systems of systems: the first is an urban traffic control and monitoring system, and the second is an animal production monitoring and control system. The main contributions of this work are the presentation of the concepts, phases, activities, elements and guidelines of the MORE-SoS approach, and the specifications of the two systems present in the case studies
Keywords: Engenharia de requisitos; Sistema de sistemas; Engenharia orientada a modelos; Design science; Pesquisa-ação; Requirements engineering; System of systems; Model-driven engineering; Design science; Action research; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO